Gemoi Bite: Cookie formulation based on dandang gendis leaf extract and mocaf flour with the addition of soybean flour as a nutraceutical to stabilize blood glucose - Alfinia Ni’ma Fitriasari; Fannia Zata Brilliant; Lailatul Azizah Aprili Syahrani (Institute for Advanced Science, Social, and Sustainable Future (IASSSF), 2026)
Background: The rise in diabetes cases, coupled with the increasing prevalence of gluten intolerance, has prompted the development of gluten-free nutraceutical products with the potential to stabilize blood glucose levels. The combination of Clinacanthus nutans, soybean flour, and MOCAF supports glycemic control through the synergistic action of bioactive compounds and soluble fiber that stabilize blood glucose levels. Methods: The research design used a Completely Randomized Design (CRD) with two formulation variations. The study was conducted in two stages, a preliminary phase for formulation optimization and a main experimental phase involving 30 trained panelists recruited through purposive sampling. Dandang Gendis leaves were processed via microwave-drying at 40°C to preserve bioactive compounds, while finalized cookies were subjected to standardized proximate analysis at Universitas Brawijaya and sensory evaluation using a four-point hedonic scale. Findings: The results showed that variations in the proportion of dandang gendis leaf extract and soybean flour significantly affected the ash, fat, carbohydrate, calorie content, and sensory attributes (taste, aroma, color, and texture). The flour concentration also affected most of the physicochemical and organoleptic parameters. The best formulation was obtained in formulation 2 with a combination of 15% dandang gendis leaf extract and 25% soybean flour. The physicochemical characteristics of the cookies included water content of 10.81%, protein 6.7%, fat 0.35%, carbohydrate 78.5%, ash 1.5%, energy 256.5 kcal, glycemic index 37, and active compound content of 0.4% (flavonoid 0.2%, isoflavone 0.1%, and saponin 0.1%). Conclusion: The best formulation for Gemoi Bite functional cookies is a combination of 80 g of dandang gendis leaves and 40 g of soy flour, which boasts excellent sensory qualities and blood sugar control benefits. Novelty/Originality of this article: The uniqueness of this research lies in the synergistic formulation of Clinacanthus nutans extract, soybean flour, and MOCAF to create a special nutraceutical cake for diabetes management.